Pharmacokinetic Studies of Radiopharmaceuticals - A. S. Lunev; K. A. Lunyova; O. E. Klementyeva (Регуляторные исследования и экспертиза лекарственных средств, 2022)
Pharmacokinetic (PK) studies of radiopharmaceuticals (RPs) are distinctive because of small concentrations of active ingredients. Whereas methods applicable to non-RP medicinal products cannot be used for RPs, radionuclide methods can provide an insight into radionuclide behaviour. The aim of the study was to compare approaches to pre-clinical PK evaluation of RPs and other medicinal products. The article describes the main aspects of PK studies of RPs and non-RPs, defining similarities and differences in the conduction of these studies. The authors provided examples from their own PK studies of RPs: one investigating the possibility of using 99mTc–Zoledronic acid to visualise bone pathologies in patients receiving Zometa©; and the other demonstrating the advantage of orthotopic xenograft models over heterotopic ones. According to the conclusions, methods based on ionising radiation are undeniably superior to other methods used to study the PK of medicinal products (for example, the former offer a possibility of non-invasive detection of active ingredients in the nano and/or pico range). The data obtained during PK studies can be used to characterise both the safety and functional suitability of RPs.